PERAN EMMA WATSON SEBAGAI UN WOMEN GOODWILL AMBASSADOR DALAM MENANGANI KESETARAAN GENDER DAN PEMBERDAYAAN PEREMPUAN - Izza Humaera Almisri , Nurul; Rahma Bachtiar, Farahdiba (JURNAL SIPAKALEBBI, 2022)
The authors used liberal feminism theory and the concept of celebrity diplomacy to answer the research question in this study. This research is classified as library research by using data provided by UIN Women. The aims of this study are to: 1) find out the reasons why Emma Watson was appointed as UN Women Goodwill Ambassador, 2) describe and analyze the influence of Emma Watson as UN Women Goodwill ambassador in addressing issues of gender equality and women's empowerment. The result of this research is that the authors found the fact that Emma Watson was chosen as a UN Women Goodwill Ambassador because she met the criteria as a UN Women Goodwill Ambassador in terms of having talent that is widely recognized in the field of acting and having a broad influence beyond national boundaries so that she is able to promote UN Women's values internationally. Emma Watson as the UN Women Goodwill Ambassador has a role ini realizing five focus areas that are prioritized within the UIN Women organization by making country visit to see first hand yhe inequality that occurs in poor countries, advocating for the wider community about gender equality in the speech she gave at the launch the HeForShe campaign and influencing young people through social media.